IMPACT OFAPPRAISAL SYSTEM ON EMPLOYEE PERFORMANCE: A COMPARISON OF PERMANENTAND CONTRACTUAL EMPLOYEES OF PAKISTAN TELECOMMUNICATIONS COMPANY LIMITED (PTCL) - Malik, Kamran Ahmed; Bakhtawar, Barira (European Scientific Journal, ESJ, 2014)
This research was conducted to study the impact of performance appraisal system in PTCL on employee performance. PTCL is the largest telecommunication services provider in Pakistan. PTCL was privatized in April, 2006 by selling 26 percent shares to Etisalat. The privatization of PTCL offered its employees an opportunity to quit the regular job and join on contractual basis due to higher incentives. Ever since its privatization, the permanent and contractual employees are working side by side in PTCL. There are different types of performance appraisal systems being used in PTCL for permanent and contractual employees. This research aimed at identifying different types of appraisal systems being used at PTCL for permanent and contractual employees. How the employees perceive their respective appraisal system and subsequently what are the implications on their performance? For this purpose a questionnaire was designed and data was collected from a sample of 96 people belonging to the cadre of both permanent and contractual employees. Seven hypotheses were developed regarding employees perception about their respective appraisal system and were tested through Z-test. The survey findings show strong deviations in terms of responses of permanent and contractual employees regarding their respective appraisal systems. The permanent employees showed strong resentment about their existing appraisal system. They termed it as an insignificant annual formality with no effectiveness at all based upon its weak linkage with compensation and benefits system. On the other hand, the contractual employees were found to be immensely satisfied with the implementation of their appraisal system. The main factors were found out to be a clear, strong and compelling linkage with the pay, promotion and training.